Critical Bimetallic Phosphide Layer Enables Fast Electron Transfer and Extra Energy Supply for Flexible Quasi-Solid-State Zinc Batteries - Leixin Wu; Linfeng Lv; Yibo Xiong; Wenwu Wang; Xiaoqiao Liao; Xiyao Huang; Ruiqi Song; Zhe Zhu; Yixue Duan; Lei Wang; Zeyu Ma; Jiangwang Wang; et al. (Nano-Micro Letters)
Highlights The critical bimetallic phosphide layer (CBPL) exhibits high electrical conductivity and forms heterostructures with NiCo-layered double hydroxide (NiCo-LDH), improving the electrical conductivity of the hybrid cathode (NiCo-P1.0). CBPL facilitates OH⁻ adsorption and synergizes with NiCo-LDH in electrode reactions, delivering extra energy. NiCo-P1.0 cathode delivers 286.64 mAh g⁻¹ at 1C with a retention of 72.22% at 40C. The assembled NiCo-P1.0//Zn battery achieves energy density/power density (503.62 Wh kg−1/18.62 kW kg−1). The flexible quasi-solid-state pouch cell maintains stable output after deformation.